PENINGKATAN KARAKTER DISIPLIN DAN TANGGUNG JAWAB PADA ANAK USIA 5–6 TAHUN MELALUI KEGIATAN MORNING ROUTINE CHART DI TK NEGERI 1 ATAP LAWELU - Eka Tatariasti Waruwu; Aminda Tri Handayani; Juli Yanti Harahap; Novita Friska (STKIP Subang, 2026)
This classroom action research aims to enhance the character of discipline and responsibility among children aged 5–6 years through the implementation of a Morning Routine Chart at TK Negeri 1 Atap Lawelu. The study employed the Kemmis and McTaggart model and was conducted over three cycles involving 30 children in group B (16 boys and 14 girls). Data were collected through systematic observation and documentation. The results demonstrate a significant improvement in both discipline and responsibility across the cycles, particularly in children’s ability to follow structured morning routines, comply with classroom expectations, and complete tasks independently. These findings indicate that the Morning Routine Chart is an effective pedagogical tool for fostering character development in early childhood education settings.